1999
DOI: 10.1110/ps.8.5.1032
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric characterization of oat phytochrome A: Isoforms and posttranslational modifications

Abstract: At least four mRNAs for oat phytochrome A~phyA! are present in etiolated oat tissue. The complete amino acid sequences of two phyA isoforms~A3 and A4! and the N-terminal amino acid sequence of a third isoform~A5! were deduced from cDNA sequencing~Hershey et al., 1985!. In the present study, heterogeneity of phyA on a protein level was studied by tryptic mapping using electrospray ionization mass-spectrometry~ESIMS!. The total tryptic digest of iodoacetamide-modified phyA was fractionated by gel filtration chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 43 publications
3
76
0
Order By: Relevance
“…In fact, the Ser598 phosphorylation was thought to play an active role in the phyA-mediated lightsignal transduction (Lapko et al, 1999;Park et al, 2000;Kim et al, 2002b). Here, we showed that the transgenic plants of the S598A mutant were hypersensitive to light.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…In fact, the Ser598 phosphorylation was thought to play an active role in the phyA-mediated lightsignal transduction (Lapko et al, 1999;Park et al, 2000;Kim et al, 2002b). Here, we showed that the transgenic plants of the S598A mutant were hypersensitive to light.…”
Section: Discussionmentioning
confidence: 67%
“…Ser598 phosphorylation occurs only in the Pfr form of phyA in red light-treated oat seedlings (McMichael and Lagarias, 1990;Lapko et al, 1999), whereas phosphorylation of other sites (Ser7 and Ser17) was found either Pr/Pfr indifferent or Pr specific (Lapko et al, 1996(Lapko et al, , 1997. In fact, the Ser598 phosphorylation was thought to play an active role in the phyA-mediated lightsignal transduction (Lapko et al, 1999;Park et al, 2000;Kim et al, 2002b).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations